المشاركة المتناقصة وتطبيقاتها المعاصرة : البنك الإسلامي الاردني نموذجا - كواملة، نور الدين عبدالكريم (al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2006)
This study examines the Diminishing Partnership contract, which is considered as one of the new topics in the contemporary Islamic Financing system, on both the theoretical and practical perspectives. The study also aims to find out the right jurisprudential amendment for this new type of contract, which will help in extracting a suitable legal rule for this type of contract. The study relies on the inductive and analytical methodologies in stating the various types of companies that were mentioned in the books of jurisprudence, and in tracing the new issues and topics that are related to the contract of diminishing partnership. Moreover, these methodologies were used in stating the varying contemporary opinions regarding these new issues and topics, and the juristic basis for these contemporary opinions. The study also relied on the empirical analysis in studying a form of the diminishing partnership contract implemented in the Islamic bank of Jordan for finance and investment. The study concluded that the diminishing partnership contract can be either considered as a contract of a diminishing Mudaraba or a corporation contract. Moreover, the study reached the conclusion that if certain conditions and provisions were met then the diminishing partnership contract will not be similar to a loan with interest, or al-Ĩina contract, or al-Wafā contract, or a contract that will be fulfilled in the future. Finally, the study concluded that some of the advantages of the diminishing partnership contract include realizing justice in distribution, and contributing to the economical development of the society.